S-RBD IgG Response After Second Dose of CoronaVac; Prospective Study on Health Workers - Cynthia Ayu Permatasari; Jusak Nugraha; Munawaroh Fitriah (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
COVID-19 infection causes severe acute respiratory syndrome and requires immediate action. Therefore, developing safe vaccine efficacy and new therapies has become a global priority for achieving herd immunity. Vaccination is expected to form specific antibodies against the SARS-CoV-2 spike protein that can neutralize the virus, thus preventing it from binding to its specific receptor (ACE 2 receptor). This study aimed to analyze the kinetics of antibody response to the CoronaVac vaccine after administration of the second dose vaccine. An observational analytic study with a prospective cohort approach was conducted from January to November 2021 at Dr. Soetomo General Academic Hospital, Surabaya. Two hundred fifty specimens from 50 health workers who met the inclusion criteria were measured for S-RBD IgG levels using the indirect chemiluminescence immunoassay method on the Snibe Maglumi® device. The SARS-CoV-2 S-RBD IgG levels were measured five times, such as before vaccination (day 0) and day 14, day 28, month 3, and month 6 after vaccination of the second dose of CoronaVac. The median (min-max) of S-RBD IgG levels before and after vaccination of the second dose on day 14, day 28, month 3, and month 6 were 0.43 (0.43–4.07); 109,25 (30.71–1619,42); 136,46 (19.38–725,28); 26.56 (7.64–158,65); 13.11 (0.59–8666,00) BAU/mL, respectively. There was a significant difference in S-RBD IgG levels at six months post-vaccination between the group with COVID-19 infection and those without COVID-19 disease (p < 0.001). Vaccination of the second dose of CoronaVac resulted in antibody formation; however, there was a trend of decreasing humoral immunity in the 3rd month after the second dose of CoronaVac vaccination in healthy individuals.